Staying, dropping, or switching: the impacts of bank mergers on small firms - Hans Degryse; Nancy Masschelein; Janet Mitchell (National Bank of Belgium, 2009)
Assessing the impacts of bank mergers on small firms requires separating borrowers with single versus multiple banking relationships and distinguishing the three alternatives of "staying," "dropping," and "switching" of relationship. Single-relationship borrowers who "switch" to another bank following a merger will be less harmed than those whose relationship is "dropped" and not replaced. Using Belgian data, we find that single-relationship borrowers of target banks are more likely than other borrowers to be dropped. We track post-merger performance and show that many dropped target-bank borrowers are harmed by the merger. Multiple-relationship borrowers are less harmed, as they can better hedge against relationship discontinuations
Keywords: G21; G28; G34; 330; Bank mergers; bank lending relationships; SME loans; Bank; Fusion; Firmenkundengeschäft; KMU; Unternehmensfinanzierung; Belgien